Managing Constraints in a Machinery Company Using Theory of Constraints’ Thinking Process Tools. Case Study - Knop Krzysztof (Management Systems in Production Engineering)
The main objective of this study is to present the practical application of the Theory of Constraints (TOC) and its Thinking Process Tools (TPT) to identify, analyze, and eliminate constraints in the production department of a machinery company specializing in the production of bearing cages. A case study was used as the research method. Interviews, direct observations, and performance indicator analysis were used to identify the most critical constraints in the production department of the studied company. The research included the application of five TOC-TPT tools: Goal Tree (GT), Current Reality Tree (CRT), Evaporating Cloud (EC), Future Reality Tree (FRT), and Prerequisite Tree (PRT). These tools were used to identify organizational goals, diagnose the root causes of key constraints, resolve internal conflicts, design future solutions, and outline the path for implementing solutions. The study focused on an in-depth analysis of the key constraint in the form of the lack of work instructions at each stage of production. The analysis revealed that the root causes of this limitation were insufficient investment in training and management development. Determining a dedicated budget and resources for a structured, ongoing training and development program that aligns with the company’s strategic goals and develops both technical and interpersonal skills at all levels of staff was identified as a critical solution to this problem. The advantages and limitations of using TOC-TPT were also analyzed in response to comments from the working group participating in the study. The results showed the effectiveness of TOC-TPT in solving complex operational problems in the study company and the technical and organizational problems associated with the use of TOC thinking tools. The study indicated that strategic commitment of top management, cross-functional teamwork, and targeted training are key to the successful implementation of TOC tools. The results have practical implications for manufacturing companies seeking to improve the effectiveness and efficiency of their production systems through comprehensive constraint management.